Najafov, Alik - (:unkn) unknown (My University, 2026)
Alik Najafov Malik was born on July 1, 1957, in Padar-Chol Village, Kurdamir District, Azerbaijan. He graduated from the Faculty of Mechanics and Mathematics of Baku State University in 1979, earning the qualification of Mathematician and Mathematics Teacher. He began his professional career as a mathematics teacher in Shamakhi. From 1981 to 1983, he worked as an engineer at the Institute of Mathematics and Mechanics of the Azerbaijan National Academy of Sciences. Since 1983, he has been affiliated with the Azerbaijan University of Architecture and Construction, where he has held the positions of Engineer, Senior Laboratory Assistant, Associate Professor, and currently Professor at the Department of Higher Mathematics. In 1996, he defended his PhD dissertation entitled "Parametric Spaces of Functions with Dominant Mixed Derivatives." In 2008, he successfully defended his doctoral dissertation, "Investigation of Differential and Functional-Difference Properties of Functions in Morrey-Type Spaces," and was awarded the degree of Doctor of Sciences in Physics and Mathematics. In 2014, he received the academic title of Professor. Professor Najafov has supervised five PhD dissertations in Mathematics. He is the author of numerous scientific publications in the fields of functional analysis, differential equations, and mathematical analysis, including papers published in internationally recognized academic journals.